Study of clinical profile and management of vitreous haemorrhage - Sapna Raghuwanshi; Rashmi Kumar; Shivkumar Raghuwanshi (International Journal of Medical Research and Review, 2016)
Background: Vitreous haemorrhage is one of the common causes of visual loss. This study reports a clinical profile and management of vitreous haemorrhage in our environment, which prevent complications so as to avoid irreversible damage to sight.Methods: Medical records of all patients presenting with vitreous haemorrhage from April 2010 -to- December 2011were retrospectively reviewed.Results: Seventy five patients were reviewed out of which 78% they were males. The age range was 16-45 years. Vascular disorders (48%) and Trauma accounted for 29.33% of all the causes of vitreous haemorrhage. Sudden loss of vision (60.0%) and red curtain falling in front of eye (17.33%) were the main complaints. Patients treated by medical line of treatment showing an overall recurrence rate of 55%. Amongst the different subgroups of medical treatments the patients treated by systemic steroids showed the best result. Patients treated with photocoagulation the recurrence was 10%. Retinal and vitreoretinal fibrosis, neovascularization and were common complications.Conclusion: Awareness needs to be increased to assess the causes and risk factors of vitreous haemorrhage. Specific line of therapy was instituted in cases where etiology was established resulting in early resolution of vitreous haemorrhage, reduced recurrence rate and useful visual recovery.